FASN expression, angiogenesis and lymphangiogenesis in central and peripheral giant cell lesions - Saulo Gabriel Moreira FALCI; Ana Terezinha Marques MESQUITA; Bruno Augusto Benevenuto de ANDRADE; Joao Luiz de MIRANDA; Jorge Esquiche LEÓN; Oslei Paes de ALMEIDA; Cássio Roberto Rocha dos SANTOS (University of São Paulo, 2014)
Central giant cell lesion (CGCL) and peripheral giant cell lesion (PGCL) are non-neoplastic proliferative processes of the jaws. PGCL is a reactive process induced by irritant local factors and CGCL is an intra-osseous lesion of unknown etiology. Both lesions exhibit similar histologic features showing abundant mononuclear cells, admixed with a large number of multinucleated giant cells and a rich vascularized stroma with extravasated erythrocytes, hemosiderin deposition, and blood-filled pools. Recent studies have linked fatty acid synthase (FASN) with angiogenesis. Objective: To evaluate angiogenesis and lymphangiogenesis and their relationship with FASN expression in CGCL and PGCL. Material and Methods: Thirteen CGCL and 14 PGCL of the jaws were selected for immunoexpression of FASN; CD34 and CD105 (to assess blood microvessel density [MVD] and microvessel area [MVA]); and D2-40 (to assess lymphatic MVD and MVA). Results: Within PGCL and CGCL, MVD-CD34 was signifcantly higher than MVD-CD10S, followed by MVD-D2-40. Moreover, a signifcantly higher number of FASN-positive multinucleated giant cells than mononuclear cells were observed. Between PGCL and CGCL, only MVD-CD34 and all MVA were signifcantly higher in PGCL. Positive correlation between MVA-CD10S with FASNpositive mononuclear cells in both lesions was observed. Conclusions: Our results show both lesions exhibiting similar levels of FASN expression and neoangiogenesis, suggesting constitutive processes that regulate tissue maintenance.